HBR guide to dealing with conflict manage your emotions and move on - Gallo, Amy (Ascent Audio, 2024)
While some of us enjoy a lively debate with colleagues and others prefer to suppress our feelings over disagreements, we all struggle with conflict at work. Every day we navigate an office full of competing interests, clashing personalities, limited time and resources, and fragile egos. Sure, we share the same overarching goals as our colleagues, but we don't always agree on how to achieve them. We work differently. We rub each other the wrong way. We jockey for position. How can you deal with conflict at work in a way that is both professional and productive-where it improves both your work and your relationships? You start by understanding whether you generally seek or avoid conflict, identifying the most frequent reasons for disagreement, and knowing what approaches work for what scenarios. Then, if you decide to address a particular conflict, you use that information to plan and conduct a productive conversation. The HBR Guide to Dealing with Conflict will give you the advice you need to understand the most common sources of conflict; explore your options for addressing a disagreement; recognize whether you-and your counterpart-typically seek or avoid conflict; prepare for and engage in a difficult conversation; manage your and your counterpart's emotions; develop a resolution together; and know when to walk away.
Online resource; title from title details screen (O'Reilly, viewed February 19, 2024)
Keywords: Conflict management; Work environment; Gestion des conflits; Audiobooks; Livres audio